2023
DOI: 10.1021/acs.jpclett.3c00010
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Relevance of Quantum Confinement in the Optoelectronics of CsPbBr3 Perovskite Nanostructures

Abstract: Perovskites (PVKs) have emerged as an exciting class of semiconducting materials owing to their magnificent photophysical properties and been used in solar cells, lightemitting diodes, photodetectors, etc. The growth of multidimensional nanostructures has revealed many exciting alterations in their optoelectronic properties compared to those of their bulk counterparts. In this work, we have spotlighted the influence of quantum confinement in CsPbBr 3 PVKs like the quantum dot (PQD), nanoplatelet (PNPL), and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…Therefore, in the case of NQ, the eqs S7 and S8 allowed us to calculate the quenching rate (k q ′) and the charge transfer efficiency (η CT ) using the variation of the NC's excited state lifetimes as a function of the NQ concentration. As reported in Figure 5F, the k q ′ calculated with this method (1.36 × 10 11 M −1 s −1 ) and the high η CT (29.7%) resulted to be comparable to those obtained in the Stern− Volmer studies involving analogous redox-active quinones, as reported by Sarangi et al 53 The favorable interactions of NQ electron scavenger with the surface of the OPDA-CsPbBr 3 NCs can be considered the condicio sine qua non for testing the effectiveness of this LHP/ substrate couple in photoinduced transformations. As a proof of concept, we decided to perform the NQ photoreduction, and a stirred mixture of OPDA-CsPbBr 3 NCs, NQ, and triethylamine (TEA) as a hole scavenger was illuminated with a warm white light source under an inert atmosphere.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…Therefore, in the case of NQ, the eqs S7 and S8 allowed us to calculate the quenching rate (k q ′) and the charge transfer efficiency (η CT ) using the variation of the NC's excited state lifetimes as a function of the NQ concentration. As reported in Figure 5F, the k q ′ calculated with this method (1.36 × 10 11 M −1 s −1 ) and the high η CT (29.7%) resulted to be comparable to those obtained in the Stern− Volmer studies involving analogous redox-active quinones, as reported by Sarangi et al 53 The favorable interactions of NQ electron scavenger with the surface of the OPDA-CsPbBr 3 NCs can be considered the condicio sine qua non for testing the effectiveness of this LHP/ substrate couple in photoinduced transformations. As a proof of concept, we decided to perform the NQ photoreduction, and a stirred mixture of OPDA-CsPbBr 3 NCs, NQ, and triethylamine (TEA) as a hole scavenger was illuminated with a warm white light source under an inert atmosphere.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…The nanocrystals of CsPbBr 3 (Br-NCs) and CsPbCl 3 (Cl-NCs) are synthesized via the antisolvent recrystallization method. TEM micrographs (Figure a,c) reveal cubic shapes for both PNCs and are in line with field-emission scanning electron microscopy (FESEM) images (Figure S1). The lattice spacings of 5.8 and 4.5 Å (insets of Figure a,c) for Br-NCs and Cl-NCs reflect the high crystallinity of the structures. , The size distribution histograms (Figure e) reveal an average edge length of ∼12.7 and ∼9.1 nm for Br-NCs and Cl-NCs, respectively.…”
mentioning
confidence: 53%
“…The mentioned models and the equations are observed to be not suitable for a satisfactory fit for the observed experimental I – V traces . A better fit for PNCs is observed with the modified FN equation (a linear part at lower bias voltage and FN part at higher bias region) (eq S5), with the linear fitting representing the direct tunneling while a linear I – V is observed after addition of C 60 (Figure c) . For PNCs fitted with a modified FN equation, the linear part of I – V at low bias voltage is originated by the flow of electrons with low energy which is not sufficient to overcome the trapezoidal barrier between the two electrodes (leakage current); this case usually occurs when the barrier height (ϕ B ) is greater than the applied voltage. , As the bias voltage is increased such that the ϕ B is less than the applied voltage, the barrier between electrodes turns into a triangular one and electrons get enough energy to surpass this barrier and undergo FN tunneling. , The mechanistic explanation of this tunneling phenomenon is shown in Scheme c.…”
Section: Resultsmentioning
confidence: 97%